Clinical and Immunological Characteristics of Patients With Adenovirus Infection at Different Altitude Areas in Tibet, China - Wang, Bowen; Peng, Mengjia; Yang, Li; Li, Guokai; Yang, Jie; Yundan, Ciren; Zeng, Xiaohua; Wei, Qianqi; Han, Qi; Liu, Chang; Ding, Ke; Peng, Kaige; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background The severities of human adenovirus (HAdV) infection are diverse in different areas of Tibet, China, where a large altitude span emerges. Serious consequences may be caused by medical staff if the clinical stages and immunological conditions of patients in high-altitude areas are misjudged. However, the clinical symptoms, immunological characteristics, and environmental factors of HAdV infection patients at different altitude areas have not been well described. Methods In this retrospective, multicenter cohort study, we analyzed the data of patients who were confirmed HAdV infection by PCR tests in the General Hospital of Tibet Military Command or CDC (the Center for Disease Control and Prevention) of Tibet Military Command from January 1, 2019, to December 31, 2020. Demographic, clinical, laboratory, radiological, and epidemiological data were collected from medical records system and compared among different altitude areas. The inflammatory cytokines as well as the subsets of monocytes and regulatory T cells of patients were also obtained and analyzed in this study. Results Six hundred eighty-six patients had been identified by laboratory-confirmed HAdV infection, including the low-altitude group (n = 62), medium-altitude group (n = 206), high-altitude group (n = 230), and ultra-high-altitude group (n = 188). Referring to the environmental factors regression analysis, altitude and relative humidity were tightly associated with the number of infected patients (P < 0.01). A higher incidence rate of general pneumonia (45.7%) or severe pneumonia (8.0%) occurred in the ultra-high-altitude group (P < 0.05). The incubation period, serial interval, course of the disease, and PCR-positive duration were prolonged to various extents compared with the low-altitude group (P < 0.05). Different from those in low-altitude areas, the levels of IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, G-CSF, GM-CSF, IFN-γ, IP-10, MCP-1, TNF-α, TNF-β, and VEGF in the plasma of the ultra-high-altitude group were increased (P < 0.05), while the proportion of non-classical monocytes and regulatory T cells was decreased (P < 0.05). Conclusions The findings of this research indicated that patients with HAdV infection in high-altitude areas had severe clinical symptoms and a prolonged course of disease. During clinical works, much more attention should be paid to observe the changes in their immunological conditions. Quarantine of patients in high-altitude areas should be appropriately extended to block virus shedding.